Desentralisasi Pendidikan:Proses, Implikasi dan Pengaruhnya Terhadap Arah Pendidikan Nasional - Nur Widiantoro (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The impact of education decentralization is giving appreciation for differences in ability and local conditions and community diversity in this country. Paradigm changes the education system will requires that every actor and education providers to be proactive, critical and have the passion to want to change. Educational autonomy in the framework of regional autonomy is quite a dilemma consequences among schooling. In the one hand, schools should be independent in creating quality, on the other side of the schools should be independent in creating quality, on the other side of the school still has many shortcomings (supporta). However, in the era of educational autonomy, the school be able to compete with problem, this paper tries to give an idea about the process, the implications, the influence of decentralization of education to the direction of national education and solving problems that arise from this policy. Keywords: Education, Decentralization, National Education